TNFα receptor1 drives hypoxia-promoted invasiveness of human melanoma cells - Marconi C.; Peppicelli S.; Bianchini F.; Calorini L. (Experimental Oncology, 2013)
Aim: Oxygen deprivation leading to hypoxia represents a common feature of advanced solid tumors, able to control several aspects of tumor progression. Indeed, ability to respond to changes in oxygen partial pressure represents a hallmark of malignant cells. Aim of this study is to disclose new pathway of hypoxia-induced tumor cell invasion. Materials and Methods: Hs294T human melanoma cells were grown in a gas mixture containing 0.3 % , and used to evaluate invasion on Matrigel-coated polycarbonate filters mounted in Boyden's chambers, MMP release and expression of inflammatory receptors and their ligands. Results: We demonstrate that hypoxia promotes the expression of TNFa receptor 1 (TNFαR1) able to drive a higher ability to penetrate Matrigel-coated filters of Hs294T human melanoma cells, an effect does not mediated by hypoxia-inducible factor (HIF)-1α. Conclusion: Expression inflammatory cytokine receptors in hypoxic human melanoma cells might provide a new target for improving strategies against local and distant tumor cell diffusion. Key Words: TNFa receptor 1, Hs294T human melanoma cells, hypoxia, cell invasiveness, metalloproteinase 2 and 9.